An Analysis of Teacher Professionalism in Increasing Student Learning Interest in IPAS Learning at Primary Schools - Indriyani, Selvi; Hadiyanti, Putri Octa (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to describe teacher professionalism in enhancing students’ learning interest in IPAS (Science and Social Studies) learning at SDN 020 Pangkalan Baru, Kampar Regency. This research employed a qualitative method with a narrative inquiry approach. The research subjects included fourth-grade students, class teachers, fellow teachers, and the school principal. Data collection techniques and instruments used included interview guides, questionnaires, observation sheets, and document analysis sheets. The findings indicate that teacher professionalism at SDN 020 Pangkalan Baru is relatively good. However, there are still some shortcomings, such as limited development of learning models, inadequate skills in using laptops, and insufficient use of educational applications. These issues are also influenced by poor internet connectivity. Meanwhile, students’ interest in learning IPAS is also considered good, although some students still struggle to stay focused during classroom activities.